Recycling Strategy and Challenges Associated with Waste Management Towards Sustaining the World - Saleh, Hosam M.; Hassan, Amal I. (IntechOpen, 2023)
Recycling is an act of collecting and processing items that would otherwise be discarded as waste in order to create a new product. Recycled material is being used in an increasing number of today's products. Waste management is primarily concerned with a wide range of wastes, including industrial, biological, household, municipal, organic, biomedical, and radioactive wastes. Human activity, such as the mining and processing of basic resources, generates waste and poses health problems that can emerge both indirectly and directly. Waste mismanagement is a serious problem on an individual and a governmental level. Nowadays, the waste disposal business is struggling to adapt to globalized consumerism, a system in which things are manufactured on one continent, purchased and used on another, and disposed of on yet another. Therefore, remediation is often subject to a variety of legal criteria, but it can also be based on evaluations of human health and environmental concerns in cases where no statutory standards exist or when standards are advisory. This book discusses recycling strategies and technologies to find solutions to waste management. Chapters address such topics as biodegradable waste, the circular economy, managing industrial and nuclear waste, and much more.